REPRESENTASI NILAI PERGAULAN BEBAS REMAJA PADA FILM SERIES LITTLE MOM (E-Jurnal Medium, 2022)
Film is part of mass communication media which is often used as a medium that describes social life in society. Film as a medium, can describe and reflect situations or realities that occur in real life, or other terms are representations, namely the act of presenting or describing something, both events, people, or objects through something other than itself, usually in the form of signs or symbols. One of the films in Indonesia that raises the issue of social conflict such as juvenile promiscuity is Little Mom, the film is in the form of a film series. This research uses descriptive qualitative research with Charles Sanders Peirce's semiotic theory to see how promiscuity is described in this series. The results of this study indicate that this series has the ability to construct reality and describe the reality that occurs in society, in this case, promiscuity in adolescents.